Analysis of the competitive environment of the hotel economy Ivano-Frankivsk region - Kyrpichenkova, Oksana; Bilan, Viktoriya; Matiushenko, Raisa; Kuzmin, Oleg; Sylka, Iryna; Polovyk, Volodymyr (My University, 2021)
У статті аналізуються розвиток індустрії гостинності Івано-Франківської області, зокрема Яремчанщини, фактори, які необхідно враховувати при плануванні діяльності нового готелю. This article analyzes the development of the hospitality industry of Ivano-Frankivsk region, in particular the Yaremche region, the factors that need to be considered when planning the activities of a new hotel.
Keywords: індустрія туризму; туризм; готель; основні та додаткові послуги; споживчий ринок; конкуренція; tourism industry; tourism; hotel; basic and additional services; consumer market; competition; кафедра готельно-ресторанної справи; кафедра технології ресторанної і аюрведичної продукції